Evaluating Oral health status among children with type 1 diabetes mellitus in the age group of 10-12 years - Huddar, Sandhyarani; Mohanty, Manisha; Semwal, Mansi; Agrawal, Sonam; Biswamitra, Punita; Wasti, Amit (Journal of Neonatal Surgery, 2025)
Background: Type 1 Diabetes Mellitus (T1DM) is a chronic metabolic disorder commonly diagnosed in children and adolescents. Poor glycemic control in T1DM has been associated with increased risk of oral health complications, including dental caries, gingivitis, and periodontal disease. Early evaluation of oral health status in diabetic children is essential for preventing long-term complications. This study aimed to assess the oral health status among children aged 10-12 years with T1DM and compare it with non-diabetic peers. Materials and Methods:A cross-sectional study was conducted involving 100 children aged 10-12 years, comprising 50 diagnosed T1DM patients and 50 age- and gender-matched healthy controls. Oral health was assessed using the Decayed, Missing, and Filled Teeth (DMFT) index, Gingival Index (GI), and Plaque Index (PI). Glycemic control was evaluated using recent HbA1c values. Statistical analysis was performed using SPSS v25.0, with significance set at p < 0.05. Results:The mean DMFT score in the T1DM group was 3.8 ± 1.2, significantly higher than 2.1 ± 0.9 in the control group (p = 0.001). The average Gingival Index was 1.9 ± 0.5 in diabetic children compared to 1.2 ± 0.4 in controls (p = 0.003). Plaque Index scores were also elevated in the T1DM group (2.3 ± 0.6) relative to controls (1.5 ± 0.5, p = 0.002). A positive correlation was observed between poor glycemic control (HbA1c >8%) and higher DMFT and GI scores (r = 0.45, p = 0.01). Conclusion:Children with Type 1 Diabetes Mellitus demonstrated significantly poorer oral health status compared to non-diabetic counterparts, particularly in terms of dental caries and gingival inflammation. These findings highlight the need for integrated dental care and regular oral health monitoring as part of comprehensive diabetes management in pediatric patients